On the definition of the deformed reference surface of rubber-like shells of revolution - Yukseler, RF (ASME, 1996)
A comparative analysis of rubber-like shells of revolution which undergo arbitrarily large rotations and strains is presented. The comparison is made between two alternative definitions of the deformed reference surface: (i) The deformed reference surface is composed of the same particles as the undeformed reference surface. (ii) The deformed reference is taken as the surface of mass of the shell (the dynamic consistency condition) according to which (i) is not necessarily valid. The results obtained from she buckling analysis of circular neo-Hookean plates under radial loads using various approaches strengthen the latter definition relative to the former one.
Keywords: DEFORMATION; Mechanics